Synthesis and Antibactrial Study of New 2-Amino-5-Aryl- 1,3-Thiazole-4-Carboxylic Acid Derivatives - Al- Dulaimy, Zina K.; Kadhim, Aoras A.; Attia, Abduljabbar Kh.; Thani, Mohammed Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
2-Amino-5-aryl- 1,3-thiazole-4-carboxylic acid (A1-A3) were synthesized from the reaction of various aromatic aldehyde with dichloro acetic acid and thiourea. The synthesis of 2-[[(Saminosulfinim-idoyl)(aryl)methyl](benzoyl)amino]-5-aryl-1,3-thiazole-4-carboxylic acid (A22-A30) was perfomed starting from (A1-A3) by two steps using Schiff's base (A4-A12) prepared  from the reactant compounds (A1-A3) with different aromatic aldehyde. Finally two types of imide derivatives were obtained from reactant compounds (A1-A3) with malic anhydride (A31-A33) and phthalic anhydride (A34-A36) in the presence of glacial acetic acid. All proposed structures were supported by FT-IR and UV-Visible spectroscopic data.